Combination of Dexmedetomidine and Ketamine for Magnetic Resonance Imaging Sedation - Kim, Joong-Goo; Lee, Han-Bin; Jeon, Sang-Beom (Frontiers in Neurology, 2019)
Objectives: The use of dexmedetomidine and ketamine (DEX–KET) combination for magnetic resonance imaging (MRI) sedation has not been evaluated. We investigated the efficacy and safety of DEX–KET for sedation of patients undergoing MRI of the brain. Methods: This quasi-experimental study was conducted to compare the DEX–KET combination and midazolam for MRI sedation. We included 72 patients undergoing brain MRI following bolus injection of midazolam or DEX–KET. In August 1, 2016 a new MRI sedation protocol was implemented. After protocol implementation, bolus doses of DEX–KET were administered (DEX–KET group). Thirty-six patients from the MIDA group and 36 patients from the DEX–KET group underwent MRI sequences and were compared regarding the MRI scan time and sedation-related complications (desaturation, hypotension, cardiorespiratory arrest, and aspiration pneumonia). Results: All MRI sequences were completed for 30 patients (83.3%) from the MIDA group and for 33 patients (91.7%) from the DEX–KET group (P = 0.476). The median MRI scan time was 100.0 min (interquartile range, 87.0–111.5 min) in the MIDA group and 53.5 min (interquartile range, 45.0–60.5 min) in the DEX–KET group (P < 0.001). Complications occurred in 24 (66.7%) and 8 (22.2%) patients of the MIDA and DEX–KET group, respectively (P < 0.001). Conclusions: The efficacy of DEX–KET sedation was comparable to that of midazolam for MRI examination. DEX–KET was related to shorter scan time and lower occurrence of complications compared to midazolam.